Pengaruh Autoclave terhadap Properti Fisik dan Histopatologi Tulang: Sebuah Penelitian Dasar Rekonstruksi - WIRATNAYA, I GEDE EKA; KAMAL, ACHMAD FAUZI; PATTIATA, RINO (Indonesian Journal of Cancer, 2014)
Background: Autoclave autograft is a promising alternative procedure in surgical treatment of bone tumors. A minimum effective autoclaving time of 15 minutes at 134C to devitalise tumour cells. This study aims to know the effect of autoclave to physical properties and histopathology of bone.Methods: We performed experimental study in 28 femoral bone of goat (Capra Aergagus circus) at age 1?2 year old. We divide into two groups with simple random sampling to be 14 autoclave and 14 control group. Autoclaving was performed to the bone at 134C for 15 minute. We examined physical properties each 7 autoclave group to axial and bending force compared with physical properties of the control group. We also examined histopatology of the bone both groups. Independent t-test statistical analysis to evaluate the difference of axial and bending force between autoclave and control group.Results: There were significant difference between autoclave and control group in axial force (p = 0.000) and bending force (p = 0.03). Physical properties of autoclave bone decreased 58.58 % in axial force and 20.33% bending force to control group. Histopathology examination revealed that all osteocytes were death in autoclave group but without matrix changes.Conclusion: Autoclave at 134C for 15 minute caused physical properties of bone decrease and statistically significant difference. It also made all osteocytes died but without matrix disturbance.